ANALISIS PERAN SEKOLAH DALAM MEMBENTUK KARAKTER RELIGIUS SISWA MELALUI PEMBIASAAN BACA QURAN DAN SHOLAT DUHA SEBELUM PEMBELAJARAN - Saadah, Anisah; Damayanti, Alpinah; Pradanti, Aini; Agustina, Anggi Ratna; Salim, Andi (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
he role of schools in forming religious character can make us aware of how important character is for students, especially religious character, so that students can understand and know what is good and bad and can be responsible and disciplined, especially for the young generation of the Indonesian nation. School will be the most basic knowledge for children, therefore habituation is carried out to shape children's character, especially at school. This research was conducted to analyze the influence of the school's role in pre-learning habituation on the formation of students' religious character and discipline. The research method uses a qualitative case study. The research subjects were 2 class teachers and 4 students in grades 2 & 5. Through purposive sampling. The data collection techniques used are observation, interviews, documentation. The data analysis technique uses 4 stages of data collection according to Miles & Huberman's theory. According to Miles and Huberman, namely data reduction, data presentation, drawing conclusions. The results of the research show that habituation before learning begins greatly influences the religious character of students from grade one to grade six, so schools must also continue to play an active role in encouraging this habituation so that children's character becomes stronger so that it does not just disappear.